One-day experience of pulmonary embolism response team (PERT) during the COVID-19 pandemic: three urgent percutaneous pulmonary embolectomies in acute pulmonary embolism - Łabyk, Andrzej; Potępa, Michał; Jermakow, Mateusz; Machowski, Michał; Pruszczyk, Piotr; Roik, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Percutaneous pulmonary embolectomy (PPE) is a rapidly evolving therapy in selected acute pulmonary embolism (APE) patients [1–5]. Novel percutaneous procedures tend not to be common, even in reference centers.